2022
DOI: 10.1177/15330338221144512
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Readmission After Pulmonary Resection in Patients With Lung Cancer: A Systematic Review and Meta-analysis

Abstract: Objective: Postoperative readmissions are considered an indicator of healthcare quality. The purpose of this study was to assess the factors associated with readmission following pulmonary resection for lung cancer. Methods: A comprehensive search was performed in PubMed, Web of science, the Cochrane Library, and databases of CNKI and Wanfang. We collected the factors associated with readmission following pulmonary resection from the included studies, and data analysis was conducted with STATA SE12.0 software.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Zeng et al examined 181 patients with advanced NSCLC with T2DM and suggested that hypertension may worsen their prognosis [ 69 ]. Among patients with lung cancer, another related study also suggests that hypertension is not a risk factor for postoperative readmission [ 70 ]. The differences in these results may be influenced by sample size, age of participants and the use of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al examined 181 patients with advanced NSCLC with T2DM and suggested that hypertension may worsen their prognosis [ 69 ]. Among patients with lung cancer, another related study also suggests that hypertension is not a risk factor for postoperative readmission [ 70 ]. The differences in these results may be influenced by sample size, age of participants and the use of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged PAL (pPAL), defined as PAL lasting longer than 5 days, affects 5.6–30% of patients ( 1 ). pPAL is the main reason for delayed chest tube removal, prolonged hospital stay and readmissions ( 2 - 4 ), while resulting in more complications including empyema ( 5 ), pneumonia ( 6 , 7 ) and mortality ( 8 ). Furthermore, 4.8% of patients with pPAL require additional interventions (extra chest tubes, bronchoscopy and reoperation) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%